Sejarah Mazhab Fikih di Asia Tenggara - Muhammad Ikhsan (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2018)
This study explains the historical aspects of the spread of Islamic Jurisprudence in South East Asia which cannot be separated from the history of the spread ofIslam itself in Southeast Asia. It also describes the existence of Islamic jurisprudence as indicated by the intellectual works of Southeast Asian Islamic Jurisprudence scholars, especially in the Shafi'i School. The existence of Islamic jurisprudence was then developed in the form of influences that influence the National Constitution in South East Asia, especially in Indonesia, in the form of Compilation of Islamic Law.